What Women Want: Program Design for Females Sentenced for Child Sexual Abuse - Priebe, Bricklyn (Victims & offenders, 2025)
There is a growing body of research exploring the treatment needs of females sentenced for child sexual abuse (CSA), along with an increased recognition of the importance of considering the “female” experience in correctional programming for this population. While knowledge of the gendered nuances relevant to “what” to address in program content has been explored, strategies for “how” to enhance responsivity in treatment programming for this population are less well-known. This research aimed to uncover key responsivity considerations relevant to program design and configuration for women sentenced for CSA. Interviews were conducted with justice-involved women sentenced for CSA in Australia (n = 18) and practitioners (n = 25) involved in delivering treatment. Thematic analysis revealed that flexible treatment methods, re-imagined treatment settings, and positive alliances are perceived as essential features of programs for women sentenced for CSA. Participant suggestions largely reflect practices currently used within programs for males sentenced for these offenses, and mirror international best-practice standards in correctional treatment. These findings shine light on the preferences of women who are commonly silenced in correctional research; thereby helping to inform evidence-based program development and design to enhance responsivity.